VISION OF CABLE METRO NETWORK IN ROSTOV-ON-DON - Besarion C. Meskhi; Anatoly A. Korotkiy; Valery B. Maslov (Advanced Engineering Research, 2011)
The conception of the cable metro use as the passenger transport system is considered. The investment prospects of the cable metro versus other modes of the public transport are proved. The multiengined drive with the mechatronic motion modules that opens up new vistas for the development of the passenger cable transport in the urbanized environment is described.